(untitled) (Research, Society and Development, 2024)
Tuberculosis (TB) is an infectious bacterial pathology whose basic treatment is available free of charge in the Unified Health System (SUS) and uses four medications: rifampicin, isoniazid, pyrazinamide and ethambutol. Additionally, infection with the Human Immunodeficiency Virus (HIV) increases the chance of developing TB; In this context, the combination of medications together with overlapping side effects can have an impact on quality of life and adherence to treatment. Therefore, this integrative review aimed to compare the adverse effects associated with tuberculosis treatment in patients with HIV co-infection and patients without HIV, being an observational, cross-sectional and retrospective study, with data from studies published between 2018 and 2023, using the terms ( DeCS/MeSH): “Drug-Related Side Effects and Adverse Reactions”; “Tuberculosis”; “HIV”. After carrying out the search, 16 works were selected. It was noticed that, for the most part, the adverse effects are mild, so that gastrointestinal disorders such as nausea, vomiting and pain were the most prevalent. Regarding serious issues, hepatotoxicity stood out. In patients with TB HIV co-infection, liver changes were the most common, being the group most susceptible to the development of toxic levels. Therefore, the approach to tuberculosis treatment should not be limited only to the effectiveness of the therapeutic regimen, it also requires special care regarding adverse effects and individual factors, especially in patients co-infected with HIV, aiming to maintain a balance between quality of life and success in combating the disease.